PEMBATALAN PERKAWINAN MENURUT HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Nuzha, Nuzha (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstract: This research examines the nullification of marriage based on Islamic and positive laws in Indonesia where the purpose of the research to detect the nullification of marriage based on these two kinds of law in Indonesia. It is a normative juridical. The result of the research depicts that the nullification of marriage based on Islamic law, namely, the cancellation of marriage (fasakh) due to the requirements which are not fulfilled when the marriage ceremony is held, then, it is cancelled because of the reasons that come after the marriage contract, next, the marriage held by the guardian with the prospective groom who are not a mate such as slaves with free people or adulterer with cared people, husbands “suspending” wives, do not return their wives to their parents , not make a living and wives are not willing, poor husbands are watched by trusted witnesses therefore they are unable to provide a living, it is annulled (fasakh) because of blemish area (skin patches), insanity, leprosy, infectious diseases such as syphilis, tuberculosis and others, it can be cancelled also due to the flesh grows on the genitalia of woman which obstruct the purpose of marriage (intercourse), another reason is because of ‘anah (penis doesn’t work for intercourse). Besides, the nullification marriage according to positive law in Indonesia, it is regulated by law number 1 of 1974 about marriage articles 22 to 28 and the compilation of Islamic law in chapter XI sections 70 to 76. The implementing of regulation is designed in government regulation number 9 of 1975 in chapter IV article 37 and 38. Article 22 of law number 1 of 1974 referring to marriage which states that it can be annulled if the parties do not meet the requirements to launch a marriage. Keywords: Nullification of Marriage, Islamic Law, Positive Law Abstrak: Penelitian tersebut membahas tentang pembatalan perkawinan menurut hukum Islam dan hukum positif di Indonesia dengan tujuan penelitian untuk mengetahui pembatalan perkawinan menurut hukum Islam dan hukum positif di Indonesia. Penelitian tersebut merupakan penelitian yuridis normatif. Hasil penelitian menunjukkan bahwa pembatalan perkawinan menurut hukum Islam yaitu batalnya perkawinan (fasakh) karena syarat yang tidak terpenuhi saat dilangsungkan akad nikah, batalnya perkawinan (fasakh) karena sebab yang datang setelah akad nikah, perkawinan yang diadakan oleh wali dengan calon mempelai laki-laki yang bukan jodoh misalnya budak dengan orang yang merdeka atau pezina dengan orang yag terpelihara dan lain-lain, suami “menggantung” istri, tidak memulangkan istri ke orang tua dan tidak pula memberikan nafkah dan istri tidak rela, suami miskin yang disaksikan oleh saksi yang dapat dipercaya sehingga tidak sanggup memberi nafkah, batalnya perkawinan (fasakh) karena balak (penyakit belang kulit), batalnya perkawinan (fasakh) karena gila, batalnya perkawinan (fasakh) karena kusta, batalnya perkawinan (fasakh) karena penyakit menular, seperti sipilis, TBC dan lain-lain, batalnya perkawinan (fasakh) karena daging tumbuh pada kemaluan perempuan yang menghambat maksud perkawinan (bersetubuh), batalnya perkawinan (fasakh) karena ‘anah (zakar tidak berfungsi untuk bersetubuh), sedangkan pembatalan perkawinan menurut hukum positif di Indonesia Pembatalan perkawinan diatur Undang-Undang No. 1 Tahun 1974 tentang Perkawinan Pasal 22 sampai dengan Pasal 28 dan Kompilasi Hukum Islam pada Bab XI Pasal 70 sampai dengan Pasal 76. Peraturan pelaksanaannya diatur pada Peraturan Pemerintah No. 9 Tahun 1975 pada Bab IV Pasal 37 dan Pasal 38. Pasal 22 Undang-Undang No. 1 Tahun 1974 tentang Perkawinan menyebutkan bahwa perkawinan dapat dibatalkan apabila para pihak tidak memenuhi syarat-syarat untuk melangsungkan perkawinan Kata Kunci: Pembatalan Perkawinan, Hukum Islam, Hukum Positif